Effects of skipping breakfast, lunch or dinner on subsequent postprandial blood glucose levels among healthy young adults. - Kanazawa, Chisato; Shimba, Yuki; Toyonaga, Saki; Nakamura, Fuzuki; Hosaka, Toshio (Nutrition & Metabolism, 2025)
Meal skipping has become increasingly common in modern society due to changes in lifestyle. While the adverse effects of skipping breakfast on postprandial glucose levels have been well established, less is known about the impact of skipping lunch or dinner on these levels. The aim of this study is to determine the effect of skipping breakfast, lunch, and dinner consecutively on postprandial glucose levels in healthy subjects. Thirteen healthy young adults were enrolled and instructed to consume meals freely at designated times while maintaining detailed food intake records. Participants then followed a controlled protocol in which one of the three meals was skipped for two consecutive days in a specified order, with interstitial glucose continuously monitored. Skipping lunch on both days significantly increased postprandial glucose levels at the subsequent dinner by 1.6 mmol/L compared to when lunch was consumed and breakfast was skipped (p < 0.001). In contrast, skipping dinner or breakfast did not result in significant changes in postprandial glucose levels at the following meal. We thus observed skipping each of these three meals to have different effects on subsequent postprandial blood glucose levels in the healthy subjects. Most notably, skipping lunch leads to increased postprandial blood glucose levels at dinner.